2021
DOI: 10.7554/elife.71036
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular functions and motile properties of bi-directional kinesin-5 Cin8 are regulated by neck linker docking

Abstract: In this study, we analyzed intracellular functions and motile properties of neck-linker (NL) variants of the bi-directional S. cerevisiae kinesin-5 motor, Cin8. We also examined – by modeling – the configuration of H-bonds during NL docking. Decreasing the number of stabilizing H-bonds resulted in partially functional variants, as long as a conserved backbone H-bond at the N-latch position (proposed to stabilize the docked conformation of the NL) remained intact. Elimination of this conserved H-bond resulted i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 92 publications
(196 reference statements)
0
10
0
Order By: Relevance
“…S1). These findings indicate that these variants were either defective in minus-end–directed motility and/or exhibited reduced affinity to MTs ( 12 , 29 ). Consistently, cells expressing these two variants (Cin8Δ39–69 and Cin8Δ70–75) exhibited a considerably lower percentage of short bipolar spindles compared to wt Cin8, indicating that these variants were defective in bipolar spindle assembly ( Fig.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…S1). These findings indicate that these variants were either defective in minus-end–directed motility and/or exhibited reduced affinity to MTs ( 12 , 29 ). Consistently, cells expressing these two variants (Cin8Δ39–69 and Cin8Δ70–75) exhibited a considerably lower percentage of short bipolar spindles compared to wt Cin8, indicating that these variants were defective in bipolar spindle assembly ( Fig.…”
Section: Resultsmentioning
confidence: 95%
“…We next examined the binding of wt Cin8 and NTnmd deletion to the MTs by determining the number of Cin8 motors bound to subtilisin-treated MTs compared to untreated MTs in the presence of ATP ( Fig. 7 ) ( 13 , 29 ). First, we found that on untreated MTs, the number of NTnmd mutants (Cin8Δ1–38 and Cin8Δ1–69) bound to MTs was markedly reduced compared to the wt Cin8 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations